Nursing care and satisfaction of hospitalized elderly people - de Ribamar Medeiros Lima Junior, José; de Lima Sardinha, Ana Hélia; Hisako Takase Gonçalves, Lucia; Portela Silva Coutinho, Nair; Namíbia Pereira Pasklan, Amanda; Alves dos Santos, Miriam (O Mundo da Saúde, 2015)
Aging is considered a natural and irreversible process. The rapid growth of the elderly population leads to increased demand for health services. Therefore, it is important to know the satisfaction of hospitalized elderly with nursing care. It was a descriptive, exploratory, cross-sectional and quantitative approach in São Luis. One hundred and two hospitalized elderly participated. They were hospitalized in a minimum period of five days at the President Dutra University Hospital. Most men, aged between 60 and 69 years old, married, had up to five years of study, Catholic, family income between 01 and 03 the minimum wage. The results showed good level of satisfaction of elderly with nursing care, with the highest average related to the field of trust. After the conclusion of the research it was noticed that the elderly of the president Dutra Uni- versity Hospital are satisfied with the care offered by nursing, so the elderly positively evaluated the care received showing a relationship of trust with nursing.